Review of an alternative seating for Attention Deficit Hyperactivity Disorder (ADHD) children - Mohd Zahari, Nurul Zafirah; Abdul Rahman, Julaila; Jasmani, Ismail (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
A child’s academic success is often dependent on his or her ability to attend to tasks and teacher and classroom expectations with minimal distraction. For children with Attention Deficit Hyperactivity Disorder (ADHD), one of the biggest issues faced by them is their inability to sit still and pay attention in the classroom. Without the treatment, ADHD children will facing the serious physical injuries and also may impact upon many aspects of an individual’s life, including academic difficulties, social skills problems, and strained parent child relationships. No treatment have been found to cure this disorder, but many available treatments can reduce the symptoms of ADHD. However, studies that examine the alternative treatment such as seating therapy for ADHD children are still very minimal. The purpose of this paper is to review the existing alternative seating and analyze how they use the alternative seating as an intervention for children with ADHD. The study is conducted through a literature review of books, journal articles and online resources, focusing on the intervention, improvement and treatment of ADHD children. The findings outline the effectiveness of alternative seating in treating ADHD children and how it may lead to reduce behavior problem of ADHD children. This is essential in determining future direction of alternative treatment for ADHD children to change the common treatment that come with side effects.